Access to eye care and support services among adults from minority ethnic communities living with visual impairment in the United Kingdom - Heinze, Nikki; Jones, Lee (Frontiers in Public Health, 2024)
Background Despite an increased risk of certain eye conditions which can lead to visual impairment (V.I.), there is evidence of a greater delay to treatment-seeking among adults from minority ethnic communities (MEC). MEC adults may also be underrepresented on V.I. registers, within early intervention services, and among the beneficiaries of national V.I. charities. However, much of this evidence is outdated or anecdotal. Methods This secondary analysis of V.I. Lives survey data explored use of eye health and support services and mobility aids among a matched control sample of 77 MEC and 77 adults aged 18 and over from white communities (WC). Participants were matched on age, gender, UK region and urban/rural setting. Additional subgroup analysis was conducted for Asian (n = 46) and black participants (n = 22). Results There were no significant group differences in areas such as eye health service use, registration status, contact with charities, and level of practical support received. But MEC participants were significantly more likely than WC participants to have received direct payments from social services to cover their care needs, Χ2 (1, 154) = 8.27, p = 0.004, and to use apps on their mobile for mobility, Χ2 (1, 154) = 5.75, p = 0.017. In contrast, WC participants were significantly more likely to agree that they were getting the level of emotional support to get on with their life, U = 3,638, p = 0.010, to feel confident to ask their friends for support, U = 2,416, p = 0.040, and to have a guide dog for mobility, Χ2 (1, 154) = 3.62, p = 0.057, although the latter did not reach statistical significance. Within the MEC group, Asian participants were significantly more likely than black participants to use a long cane, Χ2 (1, 68) = 7.24, p = 0.007, but they were significantly less likely to agree that they had received the right level of support when they started to experience V.I., U = 236.5, p = 0.040. Conclusion The preliminary findings suggests that there is scope to increase support provided by V.I. charities and the V.I. register, although, contrary to existing evidence, there were no statistically significant differences in eye health service use, registration status and use of wider support services. Further research is required to confirm these findings and explore reasons for differences.